DINAMIKA POLITIK NAHDLATUL ULAMA DI MANADO TAHUN 1960-1998 - Rasyid, Lisa Aisyah (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2022)
This paper examines the transformation of NU organization in Manado in 1960-1998, because studies related to Islamic organizations in Manado are still lacking. Even though historically Islamic organizations like NU have made significant contributions to the development of society, especially Muslims in Manado, from a social, religious, educational, economic, and political perspective. The importance of tracing history related to NU and its transformation in Manado, this study aims to explain how the history of the formation of NU in Manado and how was the transformation of NU in Manado from 1960-1998? This study is limited to 1960-1998, because in 1960 it is estimated that the first NU management was formed in Manado City. Meanwhile, 1998 was a year of division within the NU body in Manado City because of the NU central policy which then declared PKB as a party formed by and for NU members, but open to anyone, including non-Muslims. Historical research methods are used in this paper with heuristic stages, source verification, interpretation, and historiography. This paper shows that the formation of the NU branch in Manado is thought to have taken place in 1960 by Habib Abdurrahman Mulachele. Previously, several Islamic organizations had been established, such as Sarikat Islam (SI) in 1920, Muhammadiyah (1934), and Alkhairaat (1947). Since its formation in 1960, it was found that NU's transformation until 1998 experienced ups and downs.